2017
DOI: 10.1093/rof/rfx025
|View full text |Cite
|
Sign up to set email alerts
|

Can Socially Responsible Firms Survive Competition? An Analysis of Corporate Employee Matching Grant Schemes*

Abstract: Employee matching grant schemes are coordination mechanisms that reduce free-riding by socially-conscious employee-donors. Their prevalence demonstrates that socially-responsible firms can survive market competition. When socially-conscious employees are more productive or value working together, matching schemes can enhance employee welfare and raise more for charities without reducing investor profits. We document higher labor productivity at firms with matching schemes and that matching firms are more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The research on the relationship between CSR and CFP is saturated (e.g., References [13,14]). Many studies found that CSR can improve CFP through a variety of channels, such as labor reputation [15], customer awareness [16], labor productivity [17], and improved transparency [18]. Some studies found a negative relationship (e.g., Reference [19]), citing an agency problem or shareholder-stakeholder conflicts.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The research on the relationship between CSR and CFP is saturated (e.g., References [13,14]). Many studies found that CSR can improve CFP through a variety of channels, such as labor reputation [15], customer awareness [16], labor productivity [17], and improved transparency [18]. Some studies found a negative relationship (e.g., Reference [19]), citing an agency problem or shareholder-stakeholder conflicts.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Looking at other performance metrics, McGuire et al [3] found significant correlations between social responsibility and return on assets (ROA), Debt/Assets, Beta and standard deviation of total returns. More recent studies focus on different aspects of CSR and their impacts on firm outcomes, including labor reputation [18], customer awareness [19], labor productivity [20] and improved transparency [21]. In this study, we attempt to use numerous firm and executive characteristics to determine if consistent results can be obtained.…”
Section: Firm Performance and Corporate Social Responsibilitymentioning
confidence: 97%
“…In each case, the motivation for reporting would be similar between public and private firms, except when considering communication with dispersed investors. Figure References: b superior workforce (Surroca, Tribo, and Waddock, 2010;Bhattacharya et al, 2011), c increases intangible assets (Sharma and Vredenburg, 1998;Surroca et al, 2010;Porter and Kramer, 2011), d operating efficiency gains (Spicer and Lambdin, 2012), e enhanced attractiveness of the firm's shares (Brown-Liburd, Cohen, and Zamora, 2018;Elliott, Grant, and Rennekamp, 2017), f ability to attract the socially responsible investors [funds managed over $550bn in 2012 (Glassman, 2012) and Miralles-Quir os and Miralles-Quir os (2017) note that socially responsible investment has "grown enormously and as expanded globally in recent years. "], g increased institutional ownership and analyst following, lower cost of equity capital (Dhaliwal, Li, Tsang, and Yang, 2011;El Ghoul, Guedhami, Kwok, and Mishra, 2011;Dhaliwal, Radhakrishnan, Tsang, and Yang, 2012), h ability to signal expected future performance (Lys, Naughton, and Wang, 2015), i higher valuation judgments by investors for firms publishing CSR reports (Elliott, Jackson, Peecher, and White, 2014;Cheng, Green, and Ko, 2015), j favorable borrowing terms for CSR-active firms (Roberts, 1992;Goss and Roberts, 2011;Guiral, 2012), k enhanced ability to recruit employees (Chambers et al, 1998;Knight, 2006), l superior customer relations, which can result in increased sales (Klein and Dawar, 2004;Luo and Bhattacharya, 2006;Lev et al, 2010;Kim, 2017) and m improved community relations (Spicer and Lambdin, 2012) SAMPJ 11,1…”
Section: Improved Community Relations Mmentioning
confidence: 99%